2004
DOI: 10.1007/bf03181538
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on airflow in pathological nasal airway by PIV

Abstract: Understanding of airflow characteristics in nasal cavity is closely related with the physiological functions, like air-conditioning and smelling, and pathological aspects in nasal breathing. Several studies have utilized physical models of the healthy nasal cavity to investigate the relationship between nasal anatomy and airflow. The next step on this topic is naturally studies for disordered nasal airways and this is the main purpose of this article. Airflows in the pathological nasal airways, including nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Lack of meshing elements especially at the thin turbinates region inside the nasal cavity will cause failure in capturing nasal airflow in the crucial areas. The results showed that the grid dependency study resulted in an optimized meshing of 1,109,123 elements, and the computational results are validated with the pressure drop obtained from Kim and Son [31] and Wen et al [15, 17] as shown in Figure 5.…”
Section: Methodssupporting
confidence: 76%
“…Lack of meshing elements especially at the thin turbinates region inside the nasal cavity will cause failure in capturing nasal airflow in the crucial areas. The results showed that the grid dependency study resulted in an optimized meshing of 1,109,123 elements, and the computational results are validated with the pressure drop obtained from Kim and Son [31] and Wen et al [15, 17] as shown in Figure 5.…”
Section: Methodssupporting
confidence: 76%
“…Velocity distributions in the coronal planes provide better visualization for the direction of the main stream as shown in figure 7, where coloured levels denote the amplitude of average and RMS velocities. Flow characteristics related to abnormalities in nasal cavities can be conjectured from two-dimensional velocity and RMS data in the sagittal plane, as shown in figure 8 for the case of adenoid vegetation [8]. There are two re-circulating zones in the case of 70%, but there is only one in the case of 50% and the excessive value of RMS for the 70% adenoid vegetation case indicates the sharp increase in the flow resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Creating accurate transparent flow passages is essential for analysing the inward flow through a complex flow passage by PIV. Kim and Son [7] improved the procedure for producing a better cavity model with high-resolution computerized tomogram (CT) scan data and surface rendering and extended this work to deal with airflow in an abnormal nasal cavity with adenoid vegetation and asymmetry [8]. Some conjectures are obtained as follows: adenoid vegetation exceeding 60% causes a rapid increase in the pressure drop between nares and nasopharynx.…”
Section: Introductionmentioning
confidence: 99%
“…Fresconi et al (2003) presented experimental results on expiration flow in a symmetric bifurcation by using PIV and LIF techniques. And, Kim et al (2004) carried out an investigation on airflow in pathological nasal airway by PIV. However, the analysis on gas transfer and exchange mechanism related to flow pattern in the airways, especially at the respiratory zones from bronchioles to alveoli, has not been clarified in detail.…”
Section: Introductionmentioning
confidence: 99%